PERKEMBANGAN TATAK MOCCAK PADA MASYARAKAT SUKU PAKPAK - Agnesti Sinaga; Rithaony Hutajulu; Hubarry Gulo (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
Tatak Moccak is a Pakpak tribal martial art that is taken from the history and lifestyle of the ancestors of the Pakpak tribe, who in the past lived nomadically in the middle of the wilderness. The research method used is a qualitative method with several approaches, including data collection through fieldwork, interviews, observations, documentation, and laboratory work. The approach used is a historical approach that will reveal the origins and development of Tatak Moccak. The results obtained from this study are that Tatak Moccak is an integral part of the lifestyle of the Pakpak people who are nomadic in the mountains and forests, functioning as an essential skill for self-protection from natural and external threats, as well as training a strong and agile physique. Over time and cultural changes, the development of Tatak Moccak is classified into three main aspects, namely the cultural aspect, the entertainment aspect and the championship aspect. The dancer's costume is predominantly black with a red and white headband accent and ulos sibolang on the waist, as well as the use of Hau Era-era properties, machetes, and sticks, not only support the visuals of the performance but are also full of meaning of identity and strength in Pakpak culture.